2023
DOI: 10.3389/fenvs.2022.1097874
|View full text |Cite
|
Sign up to set email alerts
|

Research on monitoring and stability evaluation of ground subsidence in gypsum mine goaf

Abstract: The geological disasters caused by the ground deformation of the goaf have brought huge security risks to the ecological environment and society. Therefore, it is imminent to realize the effective monitoring and stability analysis of the ground deformation of the goaf. In this paper, taking the goaf of the gypsum mine in Diaodao District, Jingmen City as an example, through the investigation of the overall structure and distribution characteristics of the gypsum goaf, combined with the mechanical parameters of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…In recent years, underground goaf collapse accidents have occurred frequently in China, resulting in serious economic losses, casualties, and ecological damage 16 . In particular, a large number of underground goaf caused by large-scale mining, China has more than 9,000 stateowned coal mines, with an annual output of 9 billion tons, underground goaf reserves of billions of cubic meters, the damage to China's vegetation, water resources and land, as well as the potential impact on the environment and public health, cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, underground goaf collapse accidents have occurred frequently in China, resulting in serious economic losses, casualties, and ecological damage 16 . In particular, a large number of underground goaf caused by large-scale mining, China has more than 9,000 stateowned coal mines, with an annual output of 9 billion tons, underground goaf reserves of billions of cubic meters, the damage to China's vegetation, water resources and land, as well as the potential impact on the environment and public health, cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that underground mining aligns with the directional surface deformation and exerts a persistent and continuous impact on surface deformation. Xu et al [26][27][28][29][30][31][32][33] utilized D-InSAR, GNSS, and UAV technology to monitor surface subsidence in gypsum mines while they analyzed the stability of mined-out areas and evaluated the subsidence risk within mining regions. The study by Wang HN et al [15,[34][35][36] discovered that Persistent Scatterer Interferometric Synthetic Aperture Radar (PS-InSAR) and Small Baseline Subset Interferometric Synthetic Aperture Radar (SBAS-InSAR) technologies exhibit distinct advantages over D-InSAR technology in terms of long time-series analysis, atmospheric loss correlation, and monitoring accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…The joints of underground pipeline corridors are the weakest parts and are highly susceptible to the effects of uneven settlement (Liu et al, 2020;Jiang et al, 2020;Xie et al, 2020;Gebremedhn et al, 2019). Rigidly spliced box girder bridges under the influence of uneven settlement, the spliced section will appear the phenomenon of transverse stress peaks, which will lead to concrete cracking and damage (Xu et al, 2023). Settlement monitoring plays a crucial role in preventing geologic risks and disasters, and stochastic differential equations reliably yield shortterm settlement predictions (Guo et al, 2023).…”
Section: Introductionmentioning
confidence: 99%